2013
DOI: 10.1108/s2044-9968(2013)000006d009
|View full text |Cite
|
Sign up to set email alerts
|

The Innovative Use of Personal Smart Devices by Students to Support their Learning

Abstract: Research into the autonomous use of MP3 audio recorders by students in UK Higher Education demonstrated that students were innovative in their autonomous use of the devices. They used them to capture learning conversations from formal and informal situations to personalise and enhance their learning. However, today smartphones and other smart devices have replaced the necessity for students to carry multiply mobile devices including MP3 recorders. This chapter builds upon the earlier work and presents a small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
(31 reference statements)
1
10
0
1
Order By: Relevance
“…In this data it was evident that the tools that students use and the particular software applications that students use are important actants in the situation of group work. In common with the findings of [40] and [43] students used their phones to connect with each other and engage in team work in multiple locations, with the expectation that communication would be rapid and that responses would be quick. However these students still value face-to-face communication, and when team members do not attend meetings or are late this is problematic, which is consistent with the findings of Hassanien [30] who also reported on the difficulty that students have in arranging these important meetings.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In this data it was evident that the tools that students use and the particular software applications that students use are important actants in the situation of group work. In common with the findings of [40] and [43] students used their phones to connect with each other and engage in team work in multiple locations, with the expectation that communication would be rapid and that responses would be quick. However these students still value face-to-face communication, and when team members do not attend meetings or are late this is problematic, which is consistent with the findings of Hassanien [30] who also reported on the difficulty that students have in arranging these important meetings.…”
Section: Discussionmentioning
confidence: 53%
“…Access to mobile phones is seemingly ubiquitous with research showing that 96.4% of first year students in Melbourne had a mobile phone [37] and mobile phones are superseding other technologies such as dedicated ÔclickersÕ in lectures [38]) Smart phones make it possible for pervasive access to learning Òanytime, anywhereÓ [39]; facilitate multitasking behavior [40], and provide opportunities for collaboration and discussion with classmates and tutors that is supportive of a constructivist pedagogy [41]. Research has shown that it can be difficult for students to engage in synchronous communication, whether that is face-to-face or online; mobile phones are preferred when an immediate response if needed [10].…”
Section: Group-work In Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Using an "active engagement metric, " Fagen and Kamin (2013) found student engagement in programming computer code to increase when using tablet technologies during college class discussions. Similarly, Nortcliffe and Middleton (2013) surveyed university students in the United Kingdom and their results support the idea that tablets foster autonomous, pervasive, student engagement. In their 2011 study, Loch, Galligan, Hobohm and McDonald utilized netbook tablets with volunteer students in college math courses.…”
Section: Literature Reviewmentioning
confidence: 73%
“…Ongoing research shows that students are embracing smart devices to support self‐learning. In particular, they are seeking out useful apps to improve skills such as organisation, productivity, referencing, communication and multitasking (see Nortcliffe, Clark, & Parkes, ; Nortcliffe & Middleton, ; Woodcock, Armstrong, Nortcliffe, & Middleton, ; Woodcock, Middleton, & Nortcliffe, ). Furthermore, Woodcock's, Middleton et al .…”
Section: Byod In Educationmentioning
confidence: 99%